2005
DOI: 10.1016/j.gene.2005.04.039
|View full text |Cite
|
Sign up to set email alerts
|

A DNA binding motif of meiotic recombinase Rec12 (Spo11) defined by essential glycine-202, and persistence of Rec12 protein after completion of recombination

Abstract: The Rec12 (Spo11) protein of the fission yeast Schizosaccharomyces pombe is a meiosis-specific ortholog of the catalytic subunit of type VI topoisomerases and is thought to catalyze doublestrand DNA breaks that initiate recombination. We tested the hypothesis that the rec12-117 allele affects the choice of pathways by which recombination is resolved. DNA sequence analysis revealed a single missense mutation in the coding region (rec12-G202E). The corresponding glycine-202 residue of Rec12 protein is strictly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…Interestingly, Rec12 protein persists and has been suggested to play a role in MII (DeWall et al, 2005), so there may be some additional effects of proper pairing of homologous chromosomes in the context of recombination that is independent of DDK. These results provide a caveat in the use of haploid pat1 strains to model meiotic progression.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Rec12 protein persists and has been suggested to play a role in MII (DeWall et al, 2005), so there may be some additional effects of proper pairing of homologous chromosomes in the context of recombination that is independent of DDK. These results provide a caveat in the use of haploid pat1 strains to model meiotic progression.…”
Section: Discussionmentioning
confidence: 99%
“…Our bioinformatic analyses revealed that the Spo11 gene is conserved in trypanosomes and Leishmania major but not in Leishmania infantum. It has been reported (228,229) that fission yeast Spo11 (Rec12) contains a distinct catalytic motif composed of amino acids R94, D95, Y97, and Y98 and a DNA-binding motif which is defined by glycine 202. Interestingly, these residues are conserved in L. major, T. brucei, and T. cruzi (Fig.…”
Section: Meiosis and Meiotic Recombinationmentioning
confidence: 99%
“…More recently, mutational analyses of S. cerevisiae Spo11 and the S. pombe ortholog Rec12 have confirmed the biochemical and structural similarity of Spo11 to the TopoVIA subunit (Diaz et al 2002;Sharif et al 2002;DeWall et al 2005;Nag et al 2006). In particular, residues have been identified in Spo11 and Rec12 that are equivalent to the catalytic tyrosine and acidic residues that coordinate a divalent metal ion in archaeal TopoVI.…”
Section: Spo11mentioning
confidence: 81%